Социальна реальность в социологической традиции и современных теориях: достижения и проблемы - Маринич, И. (Социология: теория, методы, маркетинг, 2001)
The theoretical-methodological pluralistic sociology makes non-contradictory and comprehensive research of social reality impossible. The analytical and prognostic possibility of the social life phenomena "descriptive classification" are limited by the high complexity of a human being and society, their informational multidimensionality, non-linearity and adaptivity in the situation of parameterical uncertainty of study object, as well as arbitrary choice and interpretation of its parameters and natural language polysemy. The search of methodology suitable for the investigation of such highly complicated and differentiated systems inevitably leads to modelling, which is an efficient and flexible research tool of wide use.